Effect of Text Messaging-based Psychiatric Nursing Program on Quality of Life in Veterans with Post-Traumatic Stress Disorder: A Randomized Controlled Trial - Asieh ‎Darvish; Naema Khodadadi-‎Hassankiadeh; Sirous Abdoosti; Mojgan Ghapandar Kashani (Shiraz University of Medical Sciences, 2019)
Background: Recurrent post-traumatic stress disorder (PTSD) can devastate the life of a veteran. Despite the widespread use of mobile learning technology in health care and nursing, few studies have examined its potential in PTSD patients and the effect on quality of life (QoL). The present study aimed to investigate the effect of a text messaging-based psychiatric nursing program on QoL in veterans with PTSD symptoms. Methods: A single-blinded, randomized, controlled trial was conducted at the outpatient clinic of Sadr Hospital in Tehran (Iran) from January 2014 to October 2015. A total of 98 veterans with PTSD who referred to the outpatient clinic of the hospital were initially assessed for eligibility to participate in the study. Based on the inclusion criteria, 66 veterans were recruited in the study and randomly allocated to a control group (n=33) and an intervention group (n=33). Due to the lost to follow-up, 9 participants (control=4, intervention=5) were excluded from the analysis phase. The intervention group received psychiatric support via short text messages for 6 months, whereas the control group received the routine hospital care. The self-rating scale for PTSD (SRS-PTSD) and the short form 36 (SF-36) were used to evaluate the severity of symptoms and the QoL, respectively. The results were analyzed using the SPSS software (version 18.0) with the Chi-square test, Fisher's exact test, independent sample t test, and paired sample t test. P<0.05 was considered statistically significant. Results: A significant improvement in PTSD (P=0.001) and QoL (P=0.001) was observed in the intervention group compared to the control group. Moreover, the recurrence frequency in the intervention group was significantly lower (P=0.03). Conclusion: The text messaging-based psychiatric nursing program reduced the severity of symptoms in veterans with PTSD and improved their QoL. Trial Registration Number: IRCT2013101214983N1